Art therapy for social justice : radical intersections - Talwar, Savneet K.; Taylor and Francis (Boca Raton, FL : Routledge, an imprint of Taylor and Francis, 2019)
Art Therapy for Social Justice seeks to open a conversation about the cultural turn in art therapy to explore the critical intersection of social change and social justice. By moving the practice of art therapy beyond standard individualized treatment models, the authors promote scholarship and dialogue that opens boundaries; they envision cross disciplinary approaches with a focus on intersectionality through the lens of black feminism, womanism, antiracism, queer theory, disability studies, and cultural theory. In particular, specific programs are highlighted that re-conceptualize art therapy practice away from a focus on pathology towards "models of caring" based on concepts of self-care, radical caring, hospitality, and restorative practice methodologies. Each chapter takes a unique perspective on the concept of "care" that is invested in wellbeing. The authors push the boundaries of what constitutes art in art therapy, re-conceptualizing notions of care and wellbeing as an ongoing process, emphasizing the importance of self-reflexivity, and reconsidering the power of language and art in trauma narratives.
part, PART I: Theoretical Framework -- chapter 1 Beyond Multiculturalism and Cultural Competence: A Social Justice Vision in Art Therapy / Savneet K. Talwar -- chapter 2 Critiquing Art Therapy: History, Science, and Representation / Savneet K. Talwar -- chapter 3 Identity Matters: Questioning Trauma and Violence through Art, Performance, and Social Practice / Savneet K. Talwar -- chapter 4 Intersectional Reflexivity: Considering Identities and Accountability for Art Therapists / Savneet K. Talwar Rumi Clinton Teresa Sit Luisa Ospina -- chapter 5 Envisioning Black Women's Consciousness in Art Therapy / Leah Gipson -- part, PART II Praxis: Public Therapeutics and Art Therapy -- chapter 6 "You Want to Be Well?" Self-Care as a Black Feminist Intervention in Art Therapy / Salamishah Tillet Scheherazade Tillet -- chapter 7 Radical Caring and Art Therapy: Decolonizing Immigration and Gender Violence Services / Sangeetha (Sangi) Ravichandran -- chapter 8 Res(crip)ting Art Therapy: Disability Culture as a Social Justice Intervention / Chun-Shan (Sandie) Yi -- chapter 9 "The Sweetness of Money": The Creatively Empowered Women (CEW) Design Studio, Feminist Pedagogy and Art Therapy / Savneet K. Talwar.
Keywords: Art therapists; Art therapy; Multiculturalism; PSYCHOLOGY / Applied Psychology; PSYCHOLOGY / Social Psychology